Genocide and deprivation: Healthcare, utilities, and economic strain for displaced University College of Applied Sciences staff post-october 7 - Barakat, Abeer; El Mashharawi, Aya KH; Supartono, Basuki (Indonesian Red Crescent Humanitarian Journal, 2024)
The October 7, 2023, Gaza genocide has caused a severe humanitarian crisis, disrupting healthcare, essential services, and economic stability for academic and administrative staff at the University College of Applied Sciences (UCAS). A quantitative survey was conducted involving 192 displaced UCAS staff to assess the impact of displacement, revealing significant hardships: 58% lack adequate healthcare access and face critical medication shortages due to Gaza’s damaged healthcare infrastructure. Utility disruptions are widespread, with 59% struggling to secure clean water and 55% facing inconsistent or no electricity, hampering their ability to work remotely. Additionally, 82% serve as primary family providers, yet 42% report a total loss of income. The collapse of income sources and lack of external job opportunities have intensified the financial strain on UCAS staff, threatening their professional and personal responsibilities. These findings underscore the urgent need for international intervention to restore Gaza's healthcare, utilities, and financial stability. Humanitarian efforts are crucial to support Gaza’s educational institutions and strengthen the resilience of displaced educators during this ongoing conflict.